The Impact of the Relocation of the National Capital City (IKN) of the Archipelago on the Increased Income of MSMEs in Balikpapan City - Indrayani, Indrayani (Journal of Applied Business, Taxation and Economics Research, 2025)
The relocation of the National Capital City (IKN) from Jakarta to East Kalimantan is a strategic policy that aims to reduce the burden on Jakarta and accelerate equitable development in Indonesia. Balikpapan City, as the closest city to the location of the IKN Nusantara, is predicted to become a new center of economic growth that opens up great opportunities for Micro, Small and Medium Enterprises (MSMEs). However, on the other hand, this relocation also poses challenges such as business competition, limited capital, and market expansion. Through the approach of economic growth theories-classical, neoclassical, endogenous, Schumpeterian, and sustainable-this study analyzes the direct and indirect impacts of the relocation of IKN on the increase in income of MSME actors in Balikpapan City. The results show that infrastructure development, increased demand for goods and services, and economic digitalization are the main supporting factors for increasing MSME income. On the other hand, limited access to capital, lack of managerial skills, and competition with businesses outside the region are significant barriers. To optimize these opportunities, adaptation strategies by MSME actors, government support in the form of training, easy access to financing, and the use of digital technology in marketing are needed. This study concludes that although there are still major challenges, the transfer of IKN has strong potential to increase the contribution of MSMEs to the local economy, provided that it is accompanied by appropriate policy interventions and sustainable guidance.